Frequency method of assessing the condition of the power line - R. E. Berezhnoy; V. M. Kozhevnikov; D. V. Petrov (Вестник Северо-Кавказского федерального университета)
Introduction. This article proposes the use of frequency analysis (monitoring) to solve the problem of determining the actual linear parameters of the power line, as well as determining the location of damage on it (assessing the condition of the power line).Materials and methods. The proposed method is based on an approach to power transmission lines as lines with distributed parameters using solutions of wave equations and expressions of secondary line parameters.Results and discussion. The practical implementation of one of the tasks of the frequency method in this article is to determine the location of damage on the long line model in the Multisim program.Conclusion. Within the framework of this article, a method for estimating the state of a power transmission line using frequency analysis is proposed.